Efficiency and safety of pharmacotherapy for postoperative pain in cardiac surgery - D. A. Sychev; T. E. Morozova; D. A. Shatskiy; E. V. Shikh (Кардиоваскулярная терапия и профилактика)
Intraoperative injury with the formation of a sternotomy wound is inevitably accompanied by postoperative pain, which has a negative effect on the postoperative period and prognosis of patients. Today, moderate and severe pain affects at least half of patients in the early postoperative period after cardiac surgery. Inadequate pain relief in the early postoperative period can lead to chronic pain, which significantly reduces the quality of life of patients. The concept of multimodal analgesia with different painkillers is a priority, effective and safe technique both after cardiac surgery and in other areas of surgery. The current review article is devoted to the analysis of efficacy and safety of various drug groups for postoperative pain relief in cardiac surgery.